2022
DOI: 10.3390/antiox11112150
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K2 (MK-7) Intercepts Keap-1/Nrf-2/HO-1 Pathway and Hinders Inflammatory/Apoptotic Signaling and Liver Aging in Naturally Aging Rat

Abstract: Aging is a naturally occurring physiological process with a deleterious impact on various body organs and humans’ well-being. The aging population is increasing worldwide, which imposes the need for the exploration of nutritional options that can intercept the impact of the aging processed on various body organs. Vitamin K2 (VK2) is a fat-soluble vitamin with emerging evidence on its therapeutic merits. In the current study, natural aging induced a significant liver deterioration with a disrupted Keap-1/Nrf-2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The Nrf2 pathway is a cellular defense mechanism that helps protect cells from oxidative stress by upregulating the expression of genes involved in antioxidant defense and detoxification. Vitamin K 2 has been shown to activate this pathway, leading to increased expression of antioxidant enzymes, including glutathione peroxidase [ 130 , 131 , 132 ]. Given the potential role of ferroptosis in COVID-19 pathogenesis and the possible link between vitamin K and ferroptosis, there is interest in exploring the potential therapeutic benefits of vitamin K in COVID-19.…”
Section: A Brief Overview Of Vitamin Kmentioning
confidence: 99%
“…The Nrf2 pathway is a cellular defense mechanism that helps protect cells from oxidative stress by upregulating the expression of genes involved in antioxidant defense and detoxification. Vitamin K 2 has been shown to activate this pathway, leading to increased expression of antioxidant enzymes, including glutathione peroxidase [ 130 , 131 , 132 ]. Given the potential role of ferroptosis in COVID-19 pathogenesis and the possible link between vitamin K and ferroptosis, there is interest in exploring the potential therapeutic benefits of vitamin K in COVID-19.…”
Section: A Brief Overview Of Vitamin Kmentioning
confidence: 99%
“…Several prior studies have reported that the morphology of the liver ( 26 ), kidneys ( 27 ) and skin ( 28 ) all change with aging, including the development of pycnotic nuclei in the liver, thinner dermal collagen fibers, lower infiltration of inflammatory cytokines in the skin, and less hemorrhaging and ballooning in the kidneys. In the present study, the senescence-delaying effects of saffron were also indicated by amelioration of the pathophysiological changes in the liver, skin and kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our experiment, VK2 could improve LPS-induced ALI. We determined the VK2 intervention dose for this experiment based on previous studies [18,19,25] and on the range of recommended VK2 intakes in each country [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicated that VK2 exerted its protective effect on ALI through the upregulation of Bcl-2 and downregulation of Caspase-3 in LPS-induced ALI. Indeed, VK2 administration has been reported to exert anti-apoptotic and anti-inflammatory effects [18,42]. Furthermore, P38 MAPK pathway has been evidenced to mediate apoptosis [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation